Effect of circulating prolactin, lactation days, and seasonal variations on first artificial insemination pregnancy rates using the PG7G protocol in dairy cows - Mufeed A. Alnimer; Mohamed A. Abedal-Majed; Mohmmad Al-Qaisi; Ahmad I. Shamoun (Veterinary World)
Background and Aim: Dairy farm profitability is linked to milk yield and reproductive efficiency. High prolactin levels during lactation can negatively impact fertility. Timed AI protocols like PG7G are used to improve pregnancy rates. This study investigates the effects of extending the voluntary waiting period (VWP) from 63 to 73 days after the PG7G protocol on reproductive parameters, including progesterone and prolactin levels, pregnancy rates, and pregnancy losses, in lactating Holstein cows during summer and winter seasons.